X - y = 0.85
x + y = 1
----------------add
2x = 1.85
x = 1.85/2
x = 0.925
x + y = 1
0.925 + y = 1
y = 1 - 0.925
y = 0.075
so ur 2 numbers are : 0.925 and 0.075
Answer:
A
Step-by-step explanation:
The form (2x-3)(5x+9) is fully factored. To determine if it is equivalent, multiply the parenthesis out.
(2x-3)(5x+9) = 10x² - 15x + 18x - 27 = 10x² + 3x - 27
Yes this is equivalent.
The solution is A.
Answer:
C. Figure out how much you need, then comparison shop using the Web and other resources.
Step-by-step explanation:
Answer:
you forgot the attachment
Step-by-step explanation:
Answer:
$5,306.04
Step-by-step explanation: